Teraflops from cyberspace. (Economist, 2000)
Part of a special section on technological innovation. Distributed computing has the potential to develop into a real business venture, with the possibility of a genuine revenue stream being created. The technology works by breaking down large computations into fragments that are distributed among computers connected to a network. The technology itself is not new and has been in use since 1980, but what is new is the scale and power that modern PCs can provide. PC users are central to the whole scheme, with fledging companies hoping to bring virtual supercomputing to the marketplace and putting their faith in the hope that once their customers try such technology, they will become hooked.